1982
DOI: 10.1021/jo00349a002
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic cyclic peptides from the marine tunicate Lissoclinum patella

Abstract: Pak B with 5% E^O in hexane at 2 mL/min as the eluant and with the UV detector at 350 nm. The retention data are shown in Table VI. The solvents were from Burdick and Jackson, and they were degassed prior to use. Nuclear Overhauser Effect (NOE) Determinations. AllNOEs were measured on a Bruker WM-250 spectrophotometer operating in the pulse-FT mode. Each sample (ca. 5 mg) was dissolved in 0.5 mL of dry deuterioacetone (Merck acetone-d6 "100% "), degassed by several freeze-pump-thaw cycles and sealed.The NOE va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
114
0
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(119 citation statements)
references
References 0 publications
2
114
0
3
Order By: Relevance
“…We previously reported that the reef sample contained patellamides A and C (29) in nearly equimolar amounts. Other patellamides were not detected as major products in the crude extract.…”
Section: Resultsmentioning
confidence: 97%
“…We previously reported that the reef sample contained patellamides A and C (29) in nearly equimolar amounts. Other patellamides were not detected as major products in the crude extract.…”
Section: Resultsmentioning
confidence: 97%
“…As part of a series of studies on the relationship between the chemical structural symmetry and the molecular conformation in cyclic peptides from marine ascidian, the crystal structure of patellamide A (1), a cytotoxic cyclic peptide from Lissoclinum patella (Ireland, Durso, Newman & Hacker, 1982) was determined by X-ray single-crystal analysis. The conformational analysis of this molecule, which has a non-C2-symmetric methyl group on one side of two C2-symmetric dihydro oxazole rings, appears to be important in considering the ~active conformation' of cytotoxic cyclic peptides from ascidian, as seen from the C2-symmetric ascidiacyclamide (2) which takes a rectangular conformation (Ishida, Tanaka, Nabae, Inoue, Kato, Hamada & Shioiri, 1988;Ishida, In, Doi, Inoue, Hamada & Shioiri, 1992).…”
Section: Commentmentioning
confidence: 99%
“…Patellamide-containing ascidians harbor cyanobacterial symbionts, Prochloron spp., that have eluded cultivation. Recently, it was shown that Prochloron didemni is responsible for synthesizing cyclic peptides 2,3 that were originally isolated from the host ascidians 4,5 . Surprisingly, single point mutations in short cassettes in the biosynthetic gene clusters resulted in a diverse product library 6 .…”
mentioning
confidence: 99%
“…The patellamides (3)(4)(5)(6)(7)(8) are biosynthesized through a unique ribosomal route 2 with some similarity to microcin pathways ( Fig. 1) 8 .…”
mentioning
confidence: 99%